Rationalising the use of cardiac catheterisation before Glenn completion. (6th March 2018) - James, Lorraine; Tandon, Animesh; Nugent, Alan; Malik, Sadia; Ramaciotti, Claudio; Greil, Gerald; Zabala, Luis; Forbess, Joseph; Hussain, Tarique
Abstract: Previous studies have shown that cardiac MRI can be used to evaluate the suitability for infants to undergo the Glenn operation after having undergone the Norwood procedure. We sought to analyse our institutional data retrospectively to identify whether such a policy would be advisable in the current era. We reviewed patients who underwent the Norwood procedure between 1 January, 2006 and 1 January, 2016. All patients undergoing evaluation for the Glenn procedure received clinical evaluation, echocardiography, and cardiac catheterisation. A total of 179 patients were identified; 154 patients (86%) survived to undergo cardiac catheterisation as part of evaluation for the Glenn, and all who were evaluated did not eventually receive the Glenn. Using said algorithm, if cardiac MRI or CT were to be used to rationalise the use of catheterisation, 26 of 154 patients would have required catheterisation after cross-sectional imaging identified vascular obstruction; 83 of 154 patients would have received cross-sectional imaging only; and 45 of 154 would have had catheterisation only. All cases that required intervention, excluding aortopulmonary collaterals, and all cases that were not suitable to progress would have been correctly identified using clinical and echocardiographic criteria in addition to cardiac cross-sectional imaging to rationalise the use of catheterisation. Thus, in cases with acceptable clinical, echocardiographic, and angiographic findings, the additional haemodynamic information from catheterisation is rarely of use for decision-making, and interventions can largely be predicted by angiographic imaging modalities.